Heritage Building Information Modelling (HBIM) and Selogriyo Temple Conservation Area Mapping in WebGIS Experience Design - Rahman, Arif; Prasetyo, Yudo; Wahyuddin, Yasser (Universitas Gadjah Mada, 2025)
Indonesia has many temples scattered throughout the archipelago, becoming important assets that need to be preserved. In accordance with Law No. 11/2010 on Cultural Heritage, preservation of cultural heritage requires documentation. The importance of documenting temples to anticipate damage is reflected in Selogriyo Temple which was affected by landslides in 1998. This research designed Heritage Building Information Modeling (HBIM) and conservation mapping of Selogriyo Temple based on WebGIS. Methods include Remote Sensing, Photogrammetry, and Geographic Information System (GIS). Secondary data in the form of 3D model of Selogriyo Temple from TLS acquisition was processed with segmentation for HBIM. HBIM WebGIS was designed using the waterfall method. HBIM WebGIS test was conducted through Validity Test, Reliability Test, and Feasibility Test of ISO 9126 standard. The results showed that segmentation using several software for divided the point cloud data into nine main parts of the temple. ArcGIS Online's CityEngine and SceneViewer software merged the sections and attributed information. Feasibility testing showed the 3D HBIM and WebGIS models were valid and reliable, with good consistency according to ISO 9126 standards. The score of each variable exceeded 70%, indicating a sufficient level of feasibility. The HBIM and WebGIS design provides information on temple construction, a reference for reconstruction, and supports the management of the Selogriyo Temple tourism area. This research product is expected to be used to anticipate future developments and advance the management of cultural heritage sites through smart heritage.